Laparoscopic Bowel Injuries Among Gynecologic Patients - Garcia, Francisco A. R. (Hindawi Publishing Corporation, 1997)
Bowel injury is an uncommon but recognized risk of operative laparoscopy. Because of the significant morbidity that can occur with this complication, it is important that clinicians be aware of its incidence, presentation, and management. This manuscript outlines the common causes of bowel injury, including herniation and traumatic bowel perforation. Management of laparoscopic bowel injuries is discussed and recommendations are made for avoidance of such complications.